Wilful blindness or blissful ignorance? The United States and the successful denucelarization of Iraq - Ryan, Maria (Taylor & Francis, 2014)
This article examines the successful denuclearization of Iraq by the International Atomic Energy Agency (IAEA) in the early 1990s and the apparent failure of the US Intelligence Community (IC) to rethink its assessments of Saddam’s desire for nuclear weapons despite Baghdad’s co-operation with the IAEA inspectors, and clear evidence from the Ongoing Monitoring and Verification team that this was a highly successful process. US policy towards Iraq, from the Clinton administration onwards, was hyper-politicized; it relied on a default, unchanging view of Saddam Hussein as a rogue leader bent on WMD acquisition and regional domination in an area that was of vital importance to the United States. The article also considers the impact of the fractious UNSCOM inspections process and argues that this was severely compromised by political intrusion, which was also ignored by the US IC in its assessments of Saddam’s intentions. Ultimately, US intelligence on Iraq was filtered for a decade through a hyper-politicized lens that tended to discount evidence from the IAEA that disproved pre-existing assumptions.